Pengaruh Pendidikan Dan Pelatihan Karyawan Terhadap Kinerja Karyawan Di Jatinangor National Golf - Nelvina Agustinus; Nissa Nurhanifah; Rosti Setiawati (STIE Bangkinang Publishing, 2023)
This study aims to determine the effect of employee education and training on employee performance at Jatinangor National Golf. The sample in this study amounted to 19 people or 10% of all Jatinangor National Golf employees and was taken using a consecutive sampling technique. The data used in this study are primary data in the form of questionnaires regarding training, education, and employee performance. The data were analyzed using descriptive analysis and statistical analysis. The results showed that partially, education has an effect on performance as evidenced by the t-count value which is greater than t-table (2.583 > 2.109), while training has no effect on performance because the t-count value is smaller than the t-table value (0.044 <2.109) . However, F count is greater than F table (14.990 > 3.59) which means that education and training together have a positive effect on employee performance. So, the better the education and training of employees, the better the performance of employees.